A Case Study of MasterMind Chess: Comparing Mouse/Keyboard Interaction with Kinect-Based Gestural Interface. (4th May 2016) - Vasiljevic, Gabriel Alves Mendes; de Miranda, Leonardo Cunha; de Miranda, Erica Esteves Cunha
Abstract : As gestural interfaces emerged as a new type of user interface, their use has been vastly explored by the entertainment industry to better immerse the player in games. Despite being mainly used in dance and sports games, little use was made of gestural interaction in more slow-paced genres, such as board games. In this work, we present a Kinect-based gestural interface for an online and multiplayer chess game and describe a case study with users with different playing skill levels. Comparing the mouse/keyboard interaction with the gesture-based interaction, the results of the activity were synthesized into lessons learned regarding general usability and design of game control mechanisms. These results could be applied to slow-paced board games like chess. Our findings indicate that gestural interfaces may not be suitable for competitive chess matches, yet it can be fun to play while using them in casual matches.